Factors Influencing The Intentions Of Singaporean Tourists To Revisit Malaysia - Ch'ng, Li Guat (2010)
The first objective of this study is to investigate the correlation between (i) social aspects, (ii) destination attractiveness and (iii) economic aspects and the tourist satisfaction. Tujuan kajian ini adalah untuk mengkaji hubungan di antara faktor kepentingan pelancongan dan kepuasan pelancong dari aspek sosial, penarikan tempat pelancongan, dan aspek ekonomi.